General Election (Election) As an Implementation of The Constitution in A Country with A Democracy System - Hudhaibi, Hasan Aulia (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This research discusses the implementation of democracy in Indonesia through its governmental and constitutional systems. The main focus of this study is on the role of the constitution, particularly the 1945 Constitution of the Republic of Indonesia, in conducting General Elections (Pemilu) as one of its constitutional mandates. This research adopts a descriptive-analytical approach to analyze how democracy is applied in the governance practices of Indonesia. Through an examination of the constitution's content and its historical development, this study identifies that the founders of the Unitary State of the Republic of Indonesia agreed to draft a written constitution, namely the 1945 Constitution. This constitution aims to guide the administration of the state in accordance with the people's aspirations, to establish good governance, and to support the enforcement of democracy and human rights. The research also explores the role of elections within the constitution as a vital mechanism for political participation. Elections are regarded as instruments to provide legal certainty in their implementation, ensuring fairness for all parties involved. In this context, the research concludes that Indonesia, as a democratic country, is an ideological and factual statement that cannot be denied. This research provides a deeper understanding of how the implementation of the constitution and elections plays a significant role in safeguarding and advancing democracy in Indonesia. The findings of this study are expected to contribute to the ongoing debates and further developments regarding political governance and democracy in Indonesia.